PMV as a thermal evaluation method for air-conditioned spaces in hot climates: a systematic review - Avelino, Alinny Dantas; Silva, Luiz Bueno da (Ciência e Natura, 2022)
The homogeneity of the subjects that were studied to produce the PMV model developed by Fanger and the evolution of the physical environment have an impact on the usability of the model. Many studies show that the PMV model does not represent the real thermal sensations of the occupants of the analyzed building. The purpose of this review is to identify and group the studies that show some discrepancy between the PMV and the opinions of the subjects concerning modern climatized field environments in hot climates around the world. The PRISMA statement was used to recover and analyze the articles, and 23 studies were selected for this review. The majority of the articles indicated that the PMV model is not suited to evaluate this kind of environment.